Understanding and caring for people with schizophrenia : fifteen clinical cases - Girgis, Ragy R.; Brucato, Gary, 1978-; Lieberman, Jeffrey A., 1948- (New York, NY : Routledge, 2021)
"This book challenges professional and public misconceptions of schizophrenia as an illness with intractable symptoms and inexorable mental deterioration, educating clinicians and researchers on the effectiveness of treatment to change the course of or prevent the onset of illness. The authors illustrate such effectiveness through fifteen case studies examining psychosis in diverse clients. These case studies are divided into the four phases of the illness-prodromal/clinical high risk, first-episode, chronic, and treatment-refractory-with accompanying analyses of the causes, symptoms, interventions and treatments. By depicting patients at different clinical stages of the illness, with accompanying explanations of how they got to that point, what might have been done to avoid - or has been done to achieve - this outcome, the reader will gain an appreciation of the nature of the illness and for the therapeutic potential of currently available treatments. Readers will learn about the various clinical aspects of schizophrenia and treatment including diagnosis, self-injury and suicide, cognitive deficits, stigma, the importance of medication, and psychosocial interventions"--
"Using Psychotherapy and Medications to Treat a Teenager with Prodromal Symptoms" -- "Persecutory Delusions and the Transition from Clinical High-Risk to Syndromal Psychosis" -- "The Heritability of Schizophrenia and Dealing with Having a Family Member with Schizophrenia" -- "The First-Episode of Psychosis and Suicide in Schizophrenia" -- "The Many Clinical Phases of Early Psychosis and the Importance of Psychoeducation and Medication Management" -- "Drug-Induced and Other Acute Psychoses in an Emergency Room Setting" -- "Impaired Functioning and Downward Shift in Functioning in Schizophrenia" -- "Fixed-False Beliefs" -- "The Capgras Delusion" -- "Violence in Schizophrenia" -- "Auditory Hallucinations and Religious Delusions" -- "Negative Symptoms and Cognitive Deficits" -- "Clozapine and Treatment-Refractory Illness" -- "Electroconvulsive Therapy in Schizophrenia" -- "Medical Conditions that can Masquerade as Schizophrenia".
OCLC-licensed vendor bibliographic record.
Keywords: Schizophrenics -- Care; Schizophrenia -- Case studies; PSYCHOLOGY / Neuropsychology; PSYCHOLOGY / Psychopathology / Schizophrenia; PSYCHOLOGY / Mental Health